920:393 Visual Sociology - Greenblat, Cathy (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We will examine and practice ways to combine the two disciplines of sociology and photography, using theories and concepts of the former and visual means of the latter to represent and to understand the social world. In short, we will explore how to use the camera as sociologist and how to sociologicall examine photographs. We will accomplish this through severl related efforts.